Theoretical foundations of glow discharge nitriding of internal local recesses on metallic surfaces - Stechyshyn, M.S.; Dykha, O.V.; Skyba, M.Ye.; Zdorenko, D.V.; Liukhovets, V.V. (Problems of Tribology, 2025)
This paper presents a comprehensive analysis of internal local recesses on metallic surfaces during glow discharge nitriding. Various types of recesses and their geometric features are studied to evaluate their impact on electric field concentration, which in turn affects the uniformity of surface modification. A field concentration criterion is introduced to quantify these effects, and an analytical framework is developed to describe the relationship between surface geometry and electric field parameters. The influence of the dimensions of internal recesses on field concentration is examined using numerical simulations. The results provide a deeper understanding of the mechanisms leading to localized variations in current density distribution on nitrided surfaces. The developed analytical tools are applicable for predicting and controlling electric field concentration indicators in glow discharge processes used for the surface modification of metallic components, which is critical for ensuring optimal mechanical and tribological properties